Revisit Intention at Klaten Tourism: A Perspective of Psychological Contract and Word of Mouth (Positive-Negative) - Putri, Tyas Eka Permata; Mangifera, Liana (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research investigates the relationship between Psychological Contract Fulfilment (PCF) and Psychological Contract Violation (PCV) on Revisit Intention to tourism destinations in Klaten. Given tourism's vital contribution to the global economy through economic growth, job creation, and cultural promotion, understanding factors that drive consumer revisit intention is crucial for enhancing revenue and reducing operational costs. Methodology: This research employs a quantitative method, utilizing purposive sampling. Data were collected via questionnaires from 170 respondents who had visited Klaten tourism, and the data analysis was conducted using SEM-PLS. Results: This study concludes that PCF enhances tourists' revisit intentions, while PCV diminishes them, highlighting the crucial mediating role of WOM. Thus, tourism managers in Klaten should prioritize fulfilling tourists' expectations to boost loyalty. Applications/Originality/Value: The novelty of this research lies in applying PCF and PCV concepts within Klaten's tourism context and exploring the mediating role of Word of Mouth (WOM) in Revisit Intention, a relatively unexplored area in existing literature.